The Stone Tidal Fish Weirs of the Molène Archipelago, Iroise Sea, Brittany, Western France: a long‐term tradition with early megalithic origins. (1st March 2018) - Gandois, Henri; Stéphan, Pierre; Cuisnier, David; Hulot, Olivia; Ehrhold, Axel; Paul, Marine; Dantec, Nicolas Le; Franzetti, Marcaurelio
Abstract: This reports on a project that combined evidence gleaned from aerial photographs, place‐names, interviews, topography, LIDAR data, and sonar bathymetry to locate stone tidal fish weirs in the Molène Archipelago. The results were verified by diver and pedestrian visual surveys. Models of Holocene sea‐level change allowed a group of possibly Late Mesolithic–Early Neolithic weirs to be recognized, with a second group broadly dated to the later Neolithic–Early Bronze Age. The construction of these long megalithic structures is compared to the funerary monuments for which the Molène Archipelago is well known, in terms of technique, cost, and societal organization. 抽象: 法国西部布列塔尼伊洛瓦斯海莫莱纳群岛的石头潮汐鱼堰:早期巨石文化下的长期传统 本文记述了-莱纳群岛石头潮汐鱼堰项目。该项目通过结合航空照片、地名、访谈、地形学、雷达数据和声纳探测法等方式收集到的证据来确定莫莱纳群岛石头潮汐鱼堰的位置。其结果得到了潜水员和地面人员实地调查的验证。全新世海平面变化模式使得一组可能-中石器时代晚期到新石器时代早期的新型围堰得以确认, 并大致确定了第二组围堰的年代-于新石器时代晚期至-铜时代早期。本文还从技术、成本、社会组织等方面将这种长型巨石建筑与莫莱纳群岛著名的墓冢建筑相比较。 关键词:潮汐围堰, 渔栅, 莫莱纳群岛, 巨石建筑, 海平面变化, 中石器时代, 新石器时代 法國西部布列塔尼伊洛瓦斯海莫萊納群島的石頭潮汐魚堰:早期巨石文化下的長期傳統 本文記述了-萊納群島石頭潮汐魚堰項目。該項目通過結合航空照片、地名、訪談、地形學、雷達數據和聲納探測法等方式收集到的證據來確定莫萊納群島石頭潮汐魚堰的位置。其結果得到了潛水員和地面人員實地調查的驗證。全新世海平面變化模式使得一組可能爲中石器時代晚期到新石器時代早期的新型圍堰得以確認, 並大致確定了第二組圍堰的年代-于新石器時代晚期至-銅時代早期。本文還從技術、成本、社會組織等方面將這種長型巨石建築與-萊納群島著名的墓冢建築相比較。 關-詞:潮汐圍堰, 漁柵, 莫萊納群島, 巨石建築, 海平面變化, 中石器時代, 新石器時代